Pelatihan dan Pendampingan Sistem Pembelajaran kepada Orang Tua Siswa Sekolah Dasar Kubu Raya - Novi Andriati; Martin Martin; Amelia Atika; Novi Wahyu Hidayati (LPPM Universitas Trunojoyo Madura, 2021)
Community service aims to describe the guidance of parents' learning towards their children in the time of adaptation of new habits in Kubu Raya Elementary School. This activity is in the form of counseling on how participants can develop parenting, especially in learning in accordance with changing times. So that the task as a parent can play an active and effective role, participants can increase the spirit of children in learning, participants can master digital-based IT and participants can create a program of children's day activities at home. This devotional activity is carried out at SDN 13 Sungai Ambawang Kubu Raya Regency, implemented smoothly and there is a change in parents in carrying out tutoring to children, it is evidenced by the increasing learning achievement of students and the formation of child learning programs. This training encourages participants to follow it and work completion more quickly and efficiently.